2016
DOI: 10.1371/journal.pone.0148284
|View full text |Cite
|
Sign up to set email alerts
|

Blinded by Beauty: Attractiveness Bias and Accurate Perceptions of Academic Performance

Abstract: Despite the old adage not to ‘judge a book by its cover’, facial cues often guide first impressions and these first impressions guide our decisions. Literature suggests there are valid facial cues that assist us in assessing someone’s health or intelligence, but such cues are overshadowed by an ‘attractiveness halo’ whereby desirable attributions are preferentially ascribed to attractive people. The impact of the attractiveness halo effect on perceptions of academic performance in the classroom is concerning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 93 publications
(113 reference statements)
2
37
0
Order By: Relevance
“…Using genetic data to examine value added measures 737 factors such as attractiveness, which could lead to confounding bias (Clifford & Walster, 1973;Talamas et al, 2016). Furthermore, teacher-rated ability is likely to be a less precise measure of ability than end-of-key-stage point scores, due to its reduced richness as a measure of attainment and therefore reduced imposed variability.…”
Section: Value-added Measuresmentioning
confidence: 99%
“…Using genetic data to examine value added measures 737 factors such as attractiveness, which could lead to confounding bias (Clifford & Walster, 1973;Talamas et al, 2016). Furthermore, teacher-rated ability is likely to be a less precise measure of ability than end-of-key-stage point scores, due to its reduced richness as a measure of attainment and therefore reduced imposed variability.…”
Section: Value-added Measuresmentioning
confidence: 99%
“…However, a person's attractiveness can bias people's first impressions about them and make them seem more or less capable than they really are. This has the potential to considerably affect a person's chances of getting a good education or job considerably (Talamas, Mavor, & Perrett, 2016). This is called the Halo Effect.…”
Section: Discussionmentioning
confidence: 99%
“…More attractive people have higher ratings of selfconfidence and often display an extroverted personality (Talamas, Mavor, & Perrett, 2016). Surprisingly, this extroverted trait can be determined after only 50 ms of exposure to a face (Talamas et al, 2016). Although many factors influence attractiveness, the current study focused specifically on facial attractiveness.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Recent research has identified important social consequences of attractiveness such as higher career success rates, more romantic interactions, and others' subjective views of the attractive individual as possessing other positive, high quality traits (Little, Jones, & DeBruine, 2011). More attractive people have higher ratings of selfconfidence and often display an extroverted personality (Talamas, Mavor, & Perrett, 2016). Surprisingly, this extroverted trait can be determined after only 50 ms of exposure to a face (Talamas et al, 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%